Overview of TRIPOLI-5, a Monte Carlo code for HPC - Mancusi Davide; Brun Emeric; Dechenaux Benjamin; Fröhlicher Kévin; Gonçalves Thomas; Jinaphanh Alexis; Kowalski Mikolaj Adam; Larmier Coline; Malvagi Fausto; Millasseau Grégory; Monange Wilfried; Petit Odile; et al. (EPJ Nuclear Sciences & Technologies)
CEA, IRSN and EDF have joined forces and started the development of the TRIPOLI-5® Monte Carlo particle transport code in 2022, with the goal of performing massively parallel simulations on hybrid computing architectures. TRIPOLI-5 benefits from the experience gained from previous investigations conducted on the PATMOS mini-app, concerning the portability of particle-transport algorithms in High Performance Computing environments. Currently, the main focus of TRIPOLI-5 is on reactor physics applications, including multi-physics feedback for stationary and non-stationary configurations. In the long run, TRIPOLI-5 will eventually cover a broader range of applications (encompassing radiation shielding and nuclear instrumentation) and thus supersede the current-generation Monte Carlo codes TRIPOLI-4®, developed at CEA, and MORET6, developed at IRSN. In this paper, we provide an overview of the current status of TRIPOLI-5 and highlight the trends for future developments.